Tectonic development of the North Patagonian Andes and their related Miocene foreland basin (41°30'-43°S) - Orts, Darío Leandro (2012)
Fil: Orts, Darío L. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina